PERLINDUNGAN HAK SPIRITUAL KONSUMEN MUSLIM DALAM PROGRAM SERTIFIKASI HALAL JALUR PERNYATAAN PELAKU USAHA (SELF DECLARE) - Rooza Meilia Anggraini; Anis Hidayatul Imtihanah; Yudhi Achmad Bashori (Justicia Islamica, 2023)
The end of the Government Regulation in Lieu Law No. 2 of 2022 concerning Job Creation significantly changes the Halal Product Guarantee Law. The Indonesian Ulema Council is no longer authorized to issue fatwas on products filed under the Self Declare program. The transition from the Fatwa Commission to the Fatwa Committee, whose members are academics and ulama, as well as the accelerated halal certification program for institutions under the Ministry of Religion, may provide opportunities for violations for both business actors and PPH assistants, potentially affecting the spiritual rights of consumers. This article examines the government's strategy for promoting the halal business through self-declaration and comprehending the notion of ensuring Muslim customers' spiritual rights in the self-declare halal certification program. This normative legal research article has a conceptual, statutory, and case approach. This research is classified as library research since it relies on library materials as a normative legal research data source. According to the study's findings, the self-declare program is one of the government's methods for achieving 10 million halal certificates by 2024. However, this program needs further evaluation, particularly in terms of supervision. If PPH assistants and business actors apply the provisions of the Law, the spiritual rights of consumers as part of their religious rights granted by the Constitution can be fulfilled.